1986
DOI: 10.1095/biolreprod34.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Fertilized and Unfertilized Ova are Transported at Different Rates by the Hamster Oviduct1

Abstract: To determine if the egg provides any clues for the regulation of ovum transport in the hamster, oocyte and embryo transport were compared. On the evening preceding ovulation, the animals were randomly assigned to one of five groups. They were caged overnight with a male of proven fertility (Group 1) or they were isolated (Group 2). Other females were artificially inseminated in both uterine horns at 2200 h either with fertile epididymal spermatozoa (Group 3), spermatozoa rendered infertile by freezing and thaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 4 publications
1
31
1
1
Order By: Relevance
“…The interaction enables the embryos of hamster (Ortiz et al, 1986), rat (Ortiz et al, 1989) and mares (Freeman et al, 1992) to modulate their rate of transport in the oviducts according to their development. Such interaction may also occur in the oviduct transport of human preimplantation embryos (Velasquez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction enables the embryos of hamster (Ortiz et al, 1986), rat (Ortiz et al, 1989) and mares (Freeman et al, 1992) to modulate their rate of transport in the oviducts according to their development. Such interaction may also occur in the oviduct transport of human preimplantation embryos (Velasquez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported for a variety of animal species that the rate of transport of fertilised and unfertilised ova in the oviduct differs e.g. in the horse (Betteridge & Mitchell 1974), hamster (Ortiz et al 1986) and rat (Viggiano et al 1992), whereas in pigs no such difference has been demonstrated (Mwanza et al 2002). It is possible that retention of unfertilised ova, which thus escaped observation, may be the reason for the discrepancy between the recovery rate at 3.5 days post mating and the number of corpora lutea and embryos at day 16.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that horse embryos produced prostaglandin E 2 (PGE 2 ), which mediates an acceleration of the transit to the uterus (Weber et al 1991a,b). In rats and hamsters, fertilized eggs reach the uterus at higher rates compared with the unfertilized eggs (Villalon et al 1982, Ortiz et al 1986). These findings illustrate that embryo transport is an interactive process between the embryos and the oviduct.…”
Section: Embryo Transportmentioning
confidence: 99%